Optical wave propagation phase for mKdV spherical electric flux density in sphere space - Körpınar, Talat; Sevgin, Fatih; Körpınar, Zeliha (Springer, 2024)
In this article, we illustrate surface flow alfa- microfluidical mKdV spherical electromotive phase in sphere space. Also, we obtain antiferromagnetic axially electrical alfa-micro-fluidical mKdV electric flux path circuit. We have electrical alfa-microfluidical geometrical mKdV free surface flow density in sphere space. Finally, we design antiferromagnetic wave propagation for alfa- microfluidical geometric mKdV surface flux density.
Keywords: Optical frame; Wave propagation; Optical surface flow flux; Electromotive phase